Novel homozygous mutation in the FANCA gene (c.2222G>A) in a Chinese girl of Fanconi anemia - Wen Xianhao; Qin Hongcheng; Liao Meiling; Guan Xianmin (Wiley, 2024)
Abstract Fanconi anemia is the most common inherited bone marrow failure syndrome. Its clinical manifestations include congenital dysplasia, bone marrow hematopoietic failure and tumor susceptibility. At present, there are 23 related gene abnormalities, among which FANCA is the most common. We report a case of a Chinese girl with bone dysplasia and aplastic anemia. The next‐generation sequencing results showed a homozygous mutation in the FANCA gene (c.2222G > A), which was predicted to be a pathogenic mutation based on protein function. This mutation at this site has not been reported in the previous literature. The diagnosis of Fanconi anemia should be determined with combined clinical, chromosome breakage test and gene sequencing results.